PEMETAAN JALUR INTERPRETASI EKOWISATA DI KAMPUNG ADAT CIREUNDEU - Rikko Rizki Ilhami; Reni Srimulyaningsih; Asep Purwanto (Wanamukti: Jurnal Penelitian Kehutanan, 2022)
Kampung Adat Cireundeu (KAC) has many potential ecotourism, one of which is located in West Coast district. Ecotourism usually has an educational value packed in the form of natural beauty and is in the countryside. The object of research is the development of tourism potentials and make the route of ecotourism Intermap in KAC. The methods of research by surveys, interviews, and GIS while the method of data analysis used is a qualitative descriptive method. The results of this research are reflected in the mapping of tourist interpretation lines in which the mapping is an ecotourism pathway that includes various tours in KAC. Ecotourism in the village of KAC is not well managed but there are already several potential to ecotourism development.